ZERO: Probabilistic Routing for Deploy and Forget Wireless Sensor Networks - Jose Carlos Pacho; Xavier Vilajosana; Jose Lopez Vicario; Angel A. Juan; Ignasi Vilajosana; Antoni Morell; Jordi Llosa (Sensors, 2010)
As Wireless Sensor Networks are being adopted by industry and agriculture for large-scale and unattended deployments, the need for reliable and energy-conservative protocols become critical. Physical and Link layer efforts for energy conservation are not mostly considered by routing protocols that put their efforts on maintaining reliability and throughput. Gradient-based routing protocols route data through most reliable links aiming to ensure 99% packet delivery. However, they suffer from the so-called ”hot spot” problem. Most reliable routes waste their energy fast, thus partitioning the network and reducing the area monitored. To cope with this ”hot spot” problem we propose ZERO a combined approach at Network and Link layers to increase network lifespan while conserving reliability levels by means of probabilistic load balancing techniques.